(untitled) (Update Dental College Journal, 2021)
Introduction: The use of Bioceramic sealer in the obduration of the root canal system has been expected by many of the previous studies. However, the clinical outcome has not yet been established. Objective: To compare the effectiveness of bioceramic and calcium hydroxide based root canal sealer in treatment of non-vital permanent teeth with periapical lesion (Periapical periodontitis). Materials and Methods: A total 100 mature permanent anterior teeth were selected after clinical and radiological examination which had non-vital pulp with periapical lesion. Clinically pulp vitality test, palpation and percussion test was performed maintaining standard procedure. Following cavity preparation and biomechanical preparation, each canal was obturated either with bioceramic (Endosequence BC) or calcium hydroxide based sealer (Sealapex, Kerr). All participants were evaluated immediately after obturation, at 3 and 6 months for the assessment of change in size of periapical lesion, condition of periodontal ligament space, lamina dura and incidence of post-operative pain, swelling. Statistical analysis was performed using Chi- square(X2) test and t-test. A value of p<0.05 was considered as statistically significant. Results: Bioceramic was more effective in reducing the lesion size than that of calcium hydroxide. At 6 months, the mean lesion size was reduced from 3.52±0.7 to 1.30±0.462 mm in Bioceramics and from 3.48±1.07 to 1.58± 0.498 mm in sealapex treated teeth.. Furthermore, 98% of bioceramic treated teeth and 94% of sealapex treated teeth showed absence of swelling. The differences between two groups were statistically significant (p<0.05). Conclusion: In this short period of study, Bioceramics based sealer seems to be more effective than calcium hydroxide based sealer in repair of periapical lesions of the nonvital teeth. Update Dent. Coll. j: 2021; 11(2): 26-31